Kualitas Fisik Silase Jerami Padi Dengan Penambahan Dosis EM4 Yang Berbeda Sebagai Pakan Ternak Ruminansia - Wiguna, Ivan A; Patty, Christian W; Fredriksz, Shirley (Universitas Pattimura, 2024)
This study aims to determine the physical quality of rice straw silage with the addition of different doses of EM4. The research was conducted at the Feed Engineering Technology Laboratory, Animal Husbandry Department, Pattimura University for 21 days. The experimental design used was a completely randomized design (CRD) consisting of 4 treatments and 4 replications, namely P0= rice straw + 0% EM4 P1= rice straw + 0.5% EM4 P2= rice straw + 1% EM4 P3= rice straw + 1.5% EM4. The variables observed were texture, color, aroma, pH, and presence or absence of mold. The results of the research showed that each treatment with additional doses of EM4 obtained good results regarding texture, color, aroma, pH, and the presence or absence of mold. The higher the dose of EM4 given, the lower the acidity (pH) value. The addition of EM4 as much as 1.5%, in this study aims to determine the physical quality of rice straw silage with the addition of EM4 giving the best results on the physical quality of rice straw silage, namely soft texture, good color (yellowish green), sour aroma, pH 4.2 and there is no fungus at all.